The effect of government expenditures on Indonesia economic growth - Nurlina Nurlina (Universitas Hayam Wuruk Perbanas, 2015)
The debate on the effect of government expenditure on economic growth has still happened in relation to classical group’s and Keynesian’s view. The aim of this study confirms the relationship, with the application of the case in Indonesia. Gov-ernment expenditures are aggregated, while economic growth is measured by gross domestic product. With time series design, the secondary data used covers the period of 2004 to 2013. At first, the data were analyzed descriptive-graphics, while the hypothesis testing using t-test. The results obtained indicate that government spending has a positive and significant influence to economic growth. Thus, spend-ing and investment forms by government as a form of fiscal policy must be done with great caution in order to avoid misallocation or inequality in the distribution of inter-sector development, given the importance of its role as a pending national economic growth.